Concurrent Physical Activity Protects Against C26 Adenocarcinoma Tumor-Mediated Cardiac and Skeletal Muscle Dysfunction and Wasting in Males - Louisa Tichy; Kimberly F. Allred; Erika T. Rezeli; Michael F. Coleman; Clinton D. Allred; Stephen D. Hursting; Traci L. Parry (Cells)
Muscle loss unresponsive to nutritional supplementation affects up to 80% of cancer patients and severely reduces survival and treatment response. Exercise may help preserve muscle mass and function, yet the translatability of preclinical methods remains questionable. This study aimed to assess how voluntary wheel running, a clinically relevant physical activity, protects skeletal and cardiac muscle against cancer-mediated dysfunction and identify underlying molecular mechanisms. Methods: BALB/c mice were assigned to sedentary nontumor-bearing (SED+NT), sedentary tumor-bearing (SED+T), wheel run nontumor-bearing (WR+NT), and wheel run tumor-bearing (WR+T). Tumor-bearing groups received 5 × 105 C26 cells; WR mice had wheel access for 4 weeks. Muscle function and tissue were analyzed for protective mechanisms. Results: SED+T mice exhibited significant fat and lean mass loss, indicating cachexia, which was prevented in WR+T mice. SED+T also showed 15% reduced grip strength and cardiac dysfunction, while WR+T preserved function. WR+T mice had lower expression of muscle wasting markers (Atrogin1, MuRF1, GDF15, GDF8/11). Physical activity also reduced tumor mass by 57% and volume by 37%. Conclusion: Voluntary wheel running confers tumor-suppressive, myoprotective, and cardioprotective effects. These findings support physical activity as a non-pharmacological strategy to combat cancer-related muscle wasting and dysfunction.